2013
DOI: 10.1088/0953-4075/46/9/095003
|View full text |Cite
|
Sign up to set email alerts
|

Isotope shift on the chlorine electron affinity revisited by an MCHF/CI approach

Abstract: Abstract. Today, the electron affinity is experimentally well known for most of the elements and is a useful guideline for developing ab initio computational methods. However, the measurements of isotope shifts on the electron affinity are limited by both resolution and sensitivity. In this context, theory eventually contributes to the knowledge and understanding of atomic structures, even though correlation plays a dominant role in negative ions properties and, particularly, in the calculation of the specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…Compared with our ab initio calculation, the discrepancies are less than 3%, which due not only to the neglected CC 1s and related higher-order correlations but also to the relativistic effect in the atomic state wave functions. The linear correlation between the convergency of the calculated transition energy and the MS factors for a given transition has been found in the B + , C − and Cl − ions [41,50,51], which also occurs in the present case.…”
Section: B Capture Of the Higher-order Correlationssupporting
confidence: 77%
See 2 more Smart Citations
“…Compared with our ab initio calculation, the discrepancies are less than 3%, which due not only to the neglected CC 1s and related higher-order correlations but also to the relativistic effect in the atomic state wave functions. The linear correlation between the convergency of the calculated transition energy and the MS factors for a given transition has been found in the B + , C − and Cl − ions [41,50,51], which also occurs in the present case.…”
Section: B Capture Of the Higher-order Correlationssupporting
confidence: 77%
“…the "MR-SD" model. It was shown that this method is capable of accounting for the electron correlation for the complex ions and atoms [32,[39][40][41][42][43].…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of CSFs increases very rapidly with the increasing number of orbitals in the active set and thus general SDTQ or SDT orbital replacements are feasible only for few-electron systems [181,182]. A way to include the most important higher-order correlation effects is to increase the MR set by adding CSFs for a certain portion p = α⊂M R c 2 α of the wave function composition [183,184]. The overall accuracy of the wave function increases as the multireference set accounts for a larger portion of the wave function.…”
Section: Capturing Higher-order Correlation Effectsmentioning
confidence: 99%
“…In the last decades, the interest in the isotope effects in negative ions has grown as the experimental techniques evolved [1,2]. In particular, the isotope shift on the electron affinity, i.e.…”
Section: Introductionmentioning
confidence: 99%